Taḥawulāt Dalālah al-Ṣidq fi al-Qur'an al-Karīm: Taḥlīl Dalāliy Wifq manhaj Toshihiko Izutsu - Ihsan Sa'dudin; Desintya Arfa Azkiyah; Abdullah Azmi; Eka Safitri (ALSINATUNA, 2025)
This study aims to examine Toshihiko Izutsu’s approach to semantic analysis of the Qur'anic text, with a focus on its methodological principles and applications. Izutsu emphasizes the necessity of understanding the relationships between concepts within the Qur'anic discourse, analyzing the primary and relational meanings of key terms, and considering the worldview that forms the cultural and religious backdrop of the text. His method relies on both synchronic and diachronic analysis, enabling a comprehensive understanding of the evolution of meanings over time. This methodology is applied to the analysis of the terms ṣidq ("truthfulness") and ṣādiqīn ("the truthful ones"). In the pre-Islamic era, their meanings were largely confined to worldly values such as honesty in speech, loyalty in fulfilling promises, and skillfulness in action. With the revelation of the Qur'an, these terms acquired a profound religious dimension, becoming associated with faith and ethical integrity. In Islamic mysticism (Sufism), ṣidq evolved into a foundational spiritual virtue, representing inner sincerity and complete devotion to God. The study concludes that Izutsu’s semantic approach reveals the dynamic nature of meaning within the Qur'anic text and illustrates how concepts evolve alongside social, cultural, and religious transformations. It underscores the significance of semantic analysis in uncovering the deeper dimensions of sacred texts, thereby offering new horizons for Qur'anic and linguistic studies.